Advanced active noise control headphone: algorithm and implementation - Shen, Xiaoyi (Nanyang Technological University, 2023)
Active noise control (ANC) is becoming increasingly important in daily life with the growing desire for a quiet environment. ANC headphones are commonly used to reduce noise while working, studying, or relaxing. A traditional ANC headphone generates the anti-noise with reference microphones, error microphones, and secondary sources, which have the same amplitude but opposite phase as the noise. However, some practical challenges in ANC headphones must be overcome, such as adaptive algorithm instability and computation complexity consideration, dynamic noise reduction in the multi-noise environment, reference signal with low reference to interference ratio, and causality constraints. This thesis presents some algorithms and implementations for dealing with these difficulties and improving the noise reduction performance of ANC headphones.